Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24021794
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein SMN as a Novel Player in Laryngeal Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) arises from the mucosal epithelium in the oral cavity, pharynx, sino-nasal region, and larynx. Laryngeal squamous cell carcinoma (LSCC) represents one-third of all head and neck cancers. Dysregulated RNA-related pathways define an important molecular signature in this aggressive carcinoma. The Survival Motor Neuron (SMN) protein regulates fundamental aspects of the RNA metabolism but, curiously, its role in cancer is virtually unknown. For the first time, here, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…These genes were MKI67, SAMD5, OR51E, CD44, ERP44 and POLK. A recent report showed substantial upregulation SMN1 transcripts and SMN protein in LSCC 34 . It remains to be seen if an increase in SMN1 transcripts in LSCC is also accompanied with the elevated expression of C2A-2B-3-4.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These genes were MKI67, SAMD5, OR51E, CD44, ERP44 and POLK. A recent report showed substantial upregulation SMN1 transcripts and SMN protein in LSCC 34 . It remains to be seen if an increase in SMN1 transcripts in LSCC is also accompanied with the elevated expression of C2A-2B-3-4.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, overexpression of SMN has been found to trigger neuroin ammation and the innate immune response in mice 33 . Recently, overexpression of SMN is recorded in patients with laryngeal squamous cell carcinoma (LSCC) 34 . Hence, a tight regulation of SMN appears to be critical for the proper function of the cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…These genes were MKI67 , SAMD5 , OR51E , CD44 , ERP44 and POLK . A recent report showed substantial upregulation of SMN1 transcripts and SMN protein in LSCC 34 . It remains to be seen if an increase in SMN1 transcripts in LSCC is also accompanied with the elevated expression of C2A–2B–3–4.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, overexpression of SMN has been found to trigger neuroinflammation and the innate immune response in mice 33 . Recently, overexpression of SMN was recorded in patients with laryngeal squamous cell carcinoma (LSCC) 34 . Hence, a tight regulation of SMN appears to be critical for the proper function of the cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of the THO complex may lead to imbalance in intracellular information transmission, affecting normal cell growth and death processes. Recent research has progressively uncovered THOC3's role in cancer development , McCormack NM and colleagues demonstrated that silencing the THOC3 gene markedly increases SMN protein levels, which regulate RNA metabolism and are closely linked to cell migration, invasion, and adhesion [22,23] . Yu T and colleagues discovered that elevated THOC3 expression leads to an increase in PFKFB4 levels, which consequently enhances glycolysis and facilitates the progression and motility of LUSC cells [24] .…”
Section: 0: Introductionmentioning
confidence: 99%